Direct communication of the spinal subarachnoid space with the rat dorsal root ganglia - Joukal, Marek; Klusáková, Ilona; Dubový, Petr (Annals of anatomy, 2016)
The anatomical position of the subarachnoid space (SAS) in relation to dorsal root ganglia (DRG) and penetration of tracer from the SAS into DRG were investigated. We used intrathecal injection of methylene blue to visualize the anatomical position of the SAS in relation to DRG and immunostaining of dipeptidyl peptidase IV (DPP-IV) for detecting arachnoid limiting the SAS. Intrathecal administration of fluorescent-conjugated dextran (fluoro-emerald; FE) was used to demonstrate direct communication between the SAS and DRG. Intrathecal injection of methylene blue and DPP-IV immunostaining revealed that SAS delimited by the arachnoid was extended up to the capsule of DRG in a fold-like recess that may reach approximately half of the DRG length. The arachnoid was found in direct contact to the neuronal body-rich area in the angle between dorsal root and DRG as well as between spinal nerve roots at DRG. Particles of FE were found in the cells of DRG capsule, satellite glial cells, interstitial space, as well as in small and medium-sized neurons after intrathecal injection. Penetration of FE from the SAS into the DRG induced an immune reaction expressed by colocalization of FE and immunofluorescence indicating antigen-presenting cells (MHC-II+), activated (ED1+) and resident (ED2+) macrophages, and activation of satellite glial cells (GFAP+). Penetration of lumbar-injected FE into the cervical DRG was greater than that into the lumbar DRG after intrathecal injection of FE into the cisterna magna. Our results demonstrate direct communication between DRG and cerebrospinal fluid in the SAS that can create another pathway for possible propagation of inflammatory and signaling molecules from DRG primary affected by peripheral nerve injury into DRG of remote spinal segments.
Keywords: Male; Rats, Wistar; Cerebrospinal Fluid; Dextrans; subarachnoidální prostor; Spinal Cord; Subarachnoid Space; Subarachnoid space; spinální ganglia; mužské pohlaví; potkani Wistar; Dorsal root ganglia; krysa rodu Rattus; Cerebrospinal fluid; Animals; mícha; Immunohistochemistry; zvířata; Rats; dextrany; Ganglia, Spinal; Macrophages; Fluoro-emerald; mozkomíšní mok